New Constructions of balanced Boolean functions with maximum algebraic immunity, high nonlinearity and optimal algebraic degree - Dheeraj Kumar Sharma (Walailak Journal of Science and Technology, 2019)
This paper consists of proposal of two constructions of balanced Boolean functions by using powers of primitive elements of